Correlation between self-perception of need for orthodontic treatment in pregnant women and the perception of oral health professionals - Zulma A. Rodriguez-Tarma; Marcos J. Carruitero (Universidad de Concepción., 2018)
Objective: To determine the correlation between the self-perception of need for orthodontic treatment in pregnant women and the perception of oral health professionals. Material and methods: a cross-sectional study was conducted with a sample of 30 pregnant women, whose self-perception of the need for orthodontic treatment was assessed through the aesthetic component of the Index of Orthodontic Treatment Need (IOTN). A panel of oral health professionals (OHP) composed by a dental surgeon and an orthodontist also evaluated the aesthetic perception for each pregnant woman, independently, using the same method. The correlation between the IOTN scores was evaluated using the Spearman's rank correlation coefficient and the resulting correlations were compared by the Eid-Gollwitzer-Schnmidt significance of correlations test. Results: A moderate-positive, statistically significant correlation was found between the IOTN of the pregnant women and those of the dental surgeon (0.507, p=0.004) and of the orthodontist (0.451, p=0.013). Between the dental surgeon and the orthodontist, the correlation was very high-positive and statistically significant (0.957, p<0.001). The OHP panel reported greater correlation than those involving the pregnant women (p<0.001). Conclusion: the perception of pregnant women of the need for orthodontic treatment increased moderately similar to the perception of the OHP. The pregnant women showed less consistency in their perception than the OHP, demonstrating low awareness of need for orthodontic treatment by pregnant women.